(untitled) (Ameghiniana, 2019)
A 20 m thick interval of the Miocene Puerto Madryn Formation, composed of nearshore to shelf mudstones and sandstones was the subject of a detailed, multiproxy study, including sedimentological and stratigraphical observations as well as marine-derived amorphous organic matter (AOM), phytoclast, terrestrial and marine palynomorph and calcareous nannofossil assessments. Three palynofacies were defined based on qualitative and quantitative analysis of the palynological organic matter. Based on their sedimentology and microfossils, the section was divided into four intervals: Interval 1 accumulated in relatively stable, warm water conditions, without salinity fluctuations, in an inner shelf; Intervals 2 and 3 show a marked upward fining trend and a progressive change towards a phytoclast-dominated (continental) palynofacies; Interval 4 represents a new reinstauration of normal marine conditions with a regressive trend. The accumulation of the finest-grained deposits on the shelf corresponds to the most continental signature of the succession which seems to contradict the classic grain-size stratigraphic trends for shallow marine sedimentary successions. We interpret this as the result of the progressive increase of fluvial, mud-laden freshwater input into the depositional system, interpreted as produced by switching of deltaic channels processes. The dinoflagellate cyst assemblages reflect overall warm-water conditions. Nevertheless, the presence of cool-water indicators species in some levels suggests the influence of Antarctic cold–waters in the area. Based on diagnostic dinoflagellate cyst and nannofossil taxa, the age of the studied interval was estimated between the Serravalian and the Tortonian.